The RBM39 degrader indisulam inhibits acute megakaryoblastic leukemia by altering the alternative splicing of ZMYND8 - Ying Yang; Zhiheng Li; Yang Yang; Peifang Xiao; Zhixu He; Zimu Zhang; Yizhen Li; Lei Shi; Xiaodong Wang; Yanfang Tao; Junjie Fan; Fenli Zhang; et al. (Cell & Bioscience)
Abstract Background Acute megakaryoblastic leukemia (AMKL) is a rare hematological malignancy in adults but children. Alternative splicing (AS) has been shown to affect hematological cancer progression, making splicing factors promising targets. Our research aims to investigate the efficacy of the molecular glue degrader indisulam, which targets the splicing factor RNA binding motif protein 39 (RBM39) in AMKL models. Results Public drug sensitivity data analysis revealed that AMKL cell lines exhibited the highest sensitivity to indisulam compared with other tumor types. Then we confirmed that RBM39 depletion by indisulam treatment induced AMKL cell cycle arrest and apoptosis. In AMKL mouse model, indisulam treatment significantly reduced the leukemic burden and prolonged the lifetime of AMKL mice. Mechanically, integration of transcriptomic and proteomic analyses revealed that indisulam-mediated RBM39 degradation resulted in AS of the transcription factor zinc finger MYND-type containing 8 (ZMYND8), an AMKL cell growth regulator. Finally, the effectiveness of indisulam depended on DDB1- and Cul4- Associated Factor 15 (DCAF15) expression because knockout of DCAF15 rescued the indisulam-induced RBM39 degradation and mis-splicing of ZMYND8. Conclusion Indisulam is a promising therapeutic candidate for AMKL and the RBM39-mediated ZMYND8 splicing plays an important role in promoting the development of AMKL.